Functional mechanisms underlying the persistence of Opuntia ficus-indica in a Mediterranean-type ecosystem after fire - Santos, Jessyca A.S.; Villadangos, Sabina; Garcia, Queila S.; Munné-Bosch, Sergi (Global ecology and conservation, 2024)
Changes in fire regime can favor invasive plants in Mediterranean-type ecosystems. The goal of this experiment was to understand the post-fire dynamics of the invasive cactus, Opuntia ficus-indica, by assessing the contribution and impact of clonal propagation and sexual reproduction on the recruitment of this species after fire. The number of O. ficus-indica new clones and seed-derived plants was estimated after a burn event in a natural area located in the western Mediterranean (Catalonia, NE Spain). Functional stress markers, relative growth rate, and contents of both growth- and stress-related phytohormones were measured. Furthermore, remaining plants damaged by fire were evaluated regarding fruit size, seed number, and viability, as well as other reproductive traits. Results showed that 95 % of the new recruits in the burned area were clones. Clones showed a higher water and chlorophyll content than seed-derived plants. The relative growth rate was consequently higher in clones than in seed-derived plants, which was also associated with higher contents of growth-related hormones (cytokinins and gibberellins) in the former. Furthermore, seeds produced by burned plants exhibited a thicker funicular envelope compared to seeds from unburned plants. It is concluded that, although clonal propagation was the main reproductive strategy observed after fire, its combination with sexual reproduction and efficient physiological strategies of survival guarantees persistence of this invasive plant species in burned areas due to an effective and fast recovery in cactus cover in the short term while contributing to the genetic variability in the population in the long term.